2016
DOI: 10.1007/s10461-016-1425-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Human Resources on Implementing an Evidence-Based HIV Prevention Intervention

Abstract: Evidence-based interventions (EBIs) often require competent staff, or human resources (HR), for implementation. The empirical evidence characterizing the influence of HR fluctuations on EBI delivery is limited and conflicting. Using the Interactive Systems Framework, we explored staff fluctuation and the subsequent influence on RESPECT, an HIV prevention EBI. Methods We conducted interviews with staff in two waves (n=53, Wave I; n=37, Wave II) in a national sample of organizations delivering RESPECT (N=29). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…RCT = data from the original RESPET randomized controlled trial (see references [ 24 , 25 ]). RESPECT case = data from the RESPECT de-adoption study (see reference [ 31 ])…”
Section: Methodsmentioning
confidence: 99%
“…RCT = data from the original RESPET randomized controlled trial (see references [ 24 , 25 ]). RESPECT case = data from the RESPECT de-adoption study (see reference [ 31 ])…”
Section: Methodsmentioning
confidence: 99%
“…Leadership support is crucial to develop capacities, especially those needed for the specific implementation of this project. The innovation-specific capacities should be expanded at the individual level (motivation and skills) and at the organizational level (human, technical, physical, and financial resources) [32,33]. Building specific capacities will allow the project to continue without further dependence on external support.…”
Section: Structural-level Barriersmentioning
confidence: 99%
“…High staff turnover led to poor recruitment and attendance. Prior research in non-dental contexts has found high turnover to have broad effects on program implementation, including implementation fidelity, reach, and sustainability [26][27][28]. Although high staff turnover directly influences the number of staff available for screening clients, we found that even with low turnover, agencies with insufficient staff size (e.g., DCOs) reported problems with increasing client recruitment efforts (e.g., attending parent/teacher conferences and registration nights), particularly when schools scheduled overlapping events.…”
Section: Workforce Capacitymentioning
confidence: 99%